Dampak Penerapan Sistem Informasi Manajemen Berbasis Scada Terhadap Efektivitas Karyawan Di PT. PLTU Belang Belang - Mutiara; Mardillah Mahmud; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
Information technology development encourages industrial organizations to adopt Management Information Systems (MIS) to improve employee performance effectiveness. One form of operational MIS application in the electricity generation sector is the use of the Supervisory Control and Data Acquisition (SCADA) system. This study aims to analyze the impact of implementing a SCADA-based Management Information System on employee effectiveness at PT PLTU Belang-Belang. This study used a quantitative approach with a survey method through distributing questionnaires to employees directly involved in SCADA operations. Data were analyzed using quantitative descriptive analysis with presentation in the form of tables and average values. The results showed that the implementation of SCADA-based MIS was in the good category with an average value of 4.15, while employee effectiveness was in the good category with an average value of 4.14. These findings indicate that the implementation of SCADA-based MIS makes a positive contribution to increasing employee work effectiveness. This research is expected to be a managerial consideration in optimizing technology-based information systems in the power generation industry environment.